The impact of income inequality on household indebtedness in euro area countries - Stefan Jestl (The Vienna Institute for International Economic Studies (wiiw), 2019)
This paper examines the impact of income inequality on consumption-related household indebtedness at the household level. Using the first wave of the Eurosystem Household Finance and Consumption Survey data, the analysis sheds light on heterogeneous effects across euro area countries. The results suggest a positive impact of income inequality on consumption-related household indebtedness in a small sample of countries. We further employ a multilevel regression model to also take country's macroeconomic characteristics into account, such as credit market and welfare state design. In this setting, we find an overall positive impact of income inequality on consumption-related household indebtedness.
Keywords: D12; D14; D31; 330; Income Inequality; Keeping Up With The Joneses; Household Indebtedness; Euro Area